2021
DOI: 10.3390/molecules26154493
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Preparation and Application of a Novel Silicon Fertilizer Using Talc and Calcium Carbonate as Starting Materials

Abstract: The deficiency of available silicon (Si) incurred by year-round agricultural and horticultural practices highlights the significance of Si fertilization for soil replenishment. This study focuses on a novel and economical route for the synthesis of Si fertilizer via the calcination method using talc and calcium carbonate (CaCO3) as starting materials. The molar ratio of talc to CaCO3 of 1:2.0, calcination temperature of 1150 °C and calcination time of 120 min were identified as the optimal conditions to maximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…However, with the increase in application rate, the growth index of Pakchoi decreased sharply, which may be related to the rise in soil pH value and salinity. Therefore, Si fertilizer may be a potential choice for improving crop yield ineffective Si-deficient soils under the control of dosage application (Wang et al, 2021). Moreover, many bacterial biologics are synthesized from solid carriers (talc or compost).…”
Section: Talcmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the increase in application rate, the growth index of Pakchoi decreased sharply, which may be related to the rise in soil pH value and salinity. Therefore, Si fertilizer may be a potential choice for improving crop yield ineffective Si-deficient soils under the control of dosage application (Wang et al, 2021). Moreover, many bacterial biologics are synthesized from solid carriers (talc or compost).…”
Section: Talcmentioning
confidence: 99%
“…Borges et al (2015) conducted a series of studies on the mechanochemical transformation of clay minerals, converting talc into a slow-release fertilizer using mechanochemical methods. Due to the fact that talc is rich in silicon (its silicon content theoretically can reach 63.3%) and contains almost no toxic heavy metals, it can be inferred that talc has the potential to be used for the preparation of silicon fertilizers (Kalantari et al , 2014; Wang et al , 2021). Pot experiment results showed that a soil Si-talc fertilizer application of 5 g kg –1 was the most effective for the growth of pak choi.…”
Section: Clay Minerals Regulate the Structure And Function Of Soilmentioning
confidence: 99%